Teaching Adults with Disabilities in the Postsecondary Setting: Examining the Experiences of Faculty Members - Tammi Summers (Adult Education Research Conference, 2008)
This phenomenological investigation explores the essence of postsecondary faculty experiences teaching adults with disabilities. Twelve participants revealed how their positive and negative experiences impacted their teaching practices and resulted in specific disability dilemmas.
Keywords: disabilities; adults; postsecondary; faculty experiences; phenomenology